Prevalence and Distribution of Dental Anomalies among a Sample of Orthodontic and Non-orthodontic Patients: A Retrospective Study - Aldhorae, Khalid A.; Altawili, Zainab M.; Assiry, Ali; Alqadasi, Basema; Al-Jawfi, Khalid A.; Hwaiti, Hisham (Wolters Kluwer, 2019)
Aims and Objectives: Dental anomalies are clinically evident abnormalities, which can lead to functional, aesthetic, and occlusal problems, which may complicate orthodontic treatment planning. The purpose of the study was to address the prevalence and distribution of dental anomalies in a group of Yemeni dental patients and to compare the presence of dental anomalies in patients seeking dental and orthodontic treatment. Materials and Methods: This retrospective study was conducted on 1675 digital panoramic radiographs for dental patients aged between 9 and 52 years, who visited orthodontic specialty centers in Sanaa, Yemen, from January 2018 to February 2019. The digital panoramic radiographs were evaluated for the prevalence and distribution of dental anomalies, such as supernumerary, hypodontia, microdontia, macrodontia, taurodontism, dens evaginatus, dens invaginatus, impaction, and dilacerations. Results: The distribution of anomalies was 30.61% among the orthodontic patients and 22.96% through non-orthodontic patients. The most frequent anomaly among the subjects was impaction (14%-47%), macrodontia (11.8%), microdontia (9.23%), hypodontia (7.48%), dilaceration (5.07%), dens evaginatus (1.91%), dens invaginatus (1.58%), hyperdontia (0.99%), and taurodontism (0.91%). Among the individuals who had dental anomalies, 57.9% of subjects showed one type of anomaly, 30.5% had two types of anomalies, whereas 11,49% had more than two types of anomalies. The selected dental anomalies in this study showed high prevalence rate among the orthodontic patients. Conclusion: Variations in data and results among different studies suggest the impact of racial, genetic, and environmental factors. The high frequency of dental anomalies emphasizes the need of early detection and diagnosis, which can be achieved through radiographic imaging, this would avoid potential orthodontic, functional, and aesthetic problems, and further emphasizes awareness to minimize any means of complexity of orthodontic and other dental problems.